1986
DOI: 10.1111/j.1469-8137.1986.tb00600.x
|View full text |Cite
|
Sign up to set email alerts
|

Greater Leaf Conductance of Well‐watered Va Mycorrhizal Rose Plants Is Not Related to Phosphorus Nutrition*

Abstract: SUMMARYPlants of Rosa hybrida L. cv. ' Samantha', grown with high or low phosphorus (P) fertilization, were inoculated with Glomus intraradices Schenck & Smith, G. deserticola Trappe, Bloss & Menge, or left non-mycorrhizal. All plants except the low-P non-mycorrhizal group had similar tissue dry weights, leaf and root surface areas, growth ratios, stomatal characteristics and P contents. The higher rate of P fertilization increased plant dry weight three-fold and leaf area four-fold in non-mycorrhizal plants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(47 citation statements)
references
References 34 publications
(38 reference statements)
3
43
1
Order By: Relevance
“…For example, leaf water potential was about 0.2 MPa lower in mycorrhizal wheat plants than in similar-sized nonmycorrhizal plants when the stomata began to close (Allen & Boosalis, 1983). Similarly, leaf water potential at stomatal closure was 0.7 MPa lower in AMF rose plants than in non-mycorrhizal plants of the same size (Auge et al, 1986).…”
Section: Leaf Water Potentialmentioning
confidence: 95%
“…For example, leaf water potential was about 0.2 MPa lower in mycorrhizal wheat plants than in similar-sized nonmycorrhizal plants when the stomata began to close (Allen & Boosalis, 1983). Similarly, leaf water potential at stomatal closure was 0.7 MPa lower in AMF rose plants than in non-mycorrhizal plants of the same size (Auge et al, 1986).…”
Section: Leaf Water Potentialmentioning
confidence: 95%
“…Increases in tissue P concentrations have been shown to account for a large amount of the VA mycorrhizal effect measured in Lp (Graham & Syvertsen, 1984) or whole plant water relations (Nelsen & Safir, 1982;Koide, 1985;Fitter, 1988), with some exceptions (Auge, Schekel & Wample, 1986).…”
Section: Phosphorus Nutrition and Lpmentioning
confidence: 99%
“…Auge! et al (1995) reported that applied P had no effect on stomata in half-dried sorghum plants, but in other studies they reported a decrease in stomatal conductance in roses (Auge! et al, 1986), and in maize under dry conditions (Auge!…”
Section: mentioning
confidence: 99%